Effects of treatment in women with gestational diabetes mellitus: systematic review and meta-analysis. (1st April 2010) - Horvath, Karl; Koch, Klaus; Jeitler, Klaus; Matyas, Eva; Bender, Ralf; Bastian, Hilda; Lange, Stefan; Siebenhofer, Andrea
Abstract : Objective To summarise the benefits and harms of treatments for women with gestational diabetes mellitus. Design Systematic review and meta-analysis of randomised controlled trials. Data sources Embase, Medline, AMED, BIOSIS, CCMed, CDMS, CDSR, CENTRAL, CINAHL, DARE, HTA, NHS EED, Heclinet, SciSearch, several publishers' databases, and reference lists of relevant secondary literature up to October 2009. Review methods Included studies were randomised controlled trials of specific treatment for gestational diabetes compared with usual care or "intensified" compared with "less intensified" specific treatment. Results Five randomised controlled trials matched the inclusion criteria for specific versus usual treatment. All studies used a two step approach with a 50 g glucose challenge test or screening for risk factors, or both, and a subsequent 75 g or 100 g oral glucose tolerance test. Meta-analyses did not show significant differences for most single end points judged to be of direct clinical importance. In women specifically treated for gestational diabetes, shoulder dystocia was significantly less common (odds ratio 0.40, 95% confidence interval 0.21 to 0.75), and one randomised controlled trial reported a significant reduction of pre-eclampsia (2.5 v 5.5%, P=0.02). For the surrogate end point of large for gestational age infants, the odds ratio was 0.48 (0.38 to 0.62). In the 13 randomised controlled trials of different intensities of specific treatments, meta-analysis showed a significant reduction of shoulder dystocia in women with more intensive treatment (0.31, 0.14 to 0.70). Conclusions Treatment for gestational diabetes, consisting of treatment to lower blood glucose concentration alone or with special obstetric care, seems to lower the risk for some perinatal complications. Decisions regarding treatment should take into account that the evidence of benefit is derived from trials for which women were selected with a two step strategy (glucose challenge test/screening for risk factors and oral glucose tolerance test).